Bheṣajakalpaḥ = Bheṣaja kalpaḥ - Bharadvāja, Bhagwan (C.C.R.I.M.H. pub. ; 32., 1977)
Pharmacological section of the Āyurvedasudhānidhi, verse work on Indic medicine according to the aurvedic tradition; critical ed.